Examining the public's awareness of bee (Hymenoptera: Apoidae: Anthophila) conservation in Canada. Issue 12 (14th October 2020) - van Vierssen Trip, Nyssa; MacPhail, Victoria J.; Colla, Sheila R.; Olivastri, Beatrice
Abstract: Understanding the general public's knowledge and perceptions of an issue can help drive action on the part of decision‐makers. Such understanding is critical when decision‐makers are faced with multiple stakeholders, which is the case with biodiversity conservation issues. We surveyed the Canadian general public using a telephone questionnaire to assess the level of knowledge and perceptions of native wild bee (Hymenoptera: Apoidea: Anthophila) health and conservation. We found that the general level of bee knowledge among participants was low. Half of participants named the non‐native managed European honeybee ( Apis mellifera Linnaeus 1758) as a wild bee, native to Canada. Over two‐thirds of participants stated the provisioning of ecosystem services (ES) is the most important reason to conserve bees. Half of participants thought the Canadian federal and provincial government should be principally responsible for bee conservation. One‐third of participants perceived no personal barriers to bee conservation and nearly one‐quarter stated they did not know how to help bee conservation efforts. Our results highlight that scientific researchers can play an important role in outreach and education and environmental non‐governmental organizations (ENGOs) can take an active lobbying role at the provincial and federal levels with respect to bee conservation.